The Anglicization of European Lexis. - Furiassi, Cristiano (John Benjamins Publishing Company, 2012)
This volume explores the lexical influence of English on European languages, a topical theme with linguistic and cultural implications. It provides an extensive introductory background to a cross-national view of English-induced lexical borrowing, posing crucial analytical questions such as what counts as an Anglicism. It also offers a typology of borrowings with examples from the languages represented: Armenian, Danish, French, German, Italian, Norwegian, Polish, Serbian, Spanish, and Swedish. The articles in this volume address general and language-specific issues related to the analysis and.